Comparison of different protocols of Morris water maze in cognitive impairment with heart failure. Issue 2 (16th January 2020) - Lu, Ziwen; Yang, Tao; Wang, Lei; Qiu, Qi; Zhao, Yizhou; Wu, Aiming; Li, Tong; Cheng, Wenkun; Wang, Baofu; Li, Yang; Yang, Jingjing; Zhao, Mingjing
Abstract: Aim: This study aimed to find a more sensitive and systematic behavioral evaluation protocol to evaluate the cognitive impairment in rats with heart failure (HF). Methods and results: An HF rat model was built by ligating the left anterior descending coronary artery. The cardiac function and structure were detected using echocardiography. Myocardial histopathological changes were observed by nitro blue tetrazolium and hematoxylin–eosin staining. The cognitive functions were evaluated using the acquisition task, probe trial, reversal test, and matching‐to‐sample test of the Morris water maze. In the probe trial, the number of times the rats in the model group crossed the platform site significantly decreased compared with that in the sham group. In the reversal test, the average latency was significantly longer in the sham group compared with the model group in the first trial but was shorter in the second and third trials. In the matching‐to‐sample test, the average latency of Trial1 increased significantly in the model group compared with the sham group, while no obvious difference was observed in Trial2. Therefore, the difference in the average latency between Trial1 and Trial2 of the model group was significantly larger. Conclusions: The cognitive impairment in rats with HF mainly reflected in the long‐term and working memory, spatial learning, and reversal learning ability. The probe trial and reversal test in the water maze may be more sensitive and preferred to evaluate cognitive function after HF. These findings would provide a brief evaluation protocol for further studies on the relationship between cognitive function and HF. Abstract : This study aimed to find a more sensitive and systematic behavioral evaluation protocol to evaluate the cognitive impairment in rats with heart failure (HF).The cognitive impairment in rats with HF mainly reflected in the long‐term and working memory, spatial learning and reversal learning ability.